Pachycrepoideus vindemmiae (Rondani) (Hymenoptera Pteromalidae) on Megaselia scalaris (Loew) (Diptera Phoridae), new host recorded in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The recovery of the parasitoid Pachycrepoideus vindemmiae (Rondani) (Hymenoptera Pteromalidae) on Piophila casei L. (Diptera Piophilidae) and on the new host Megaselia scalaris (Loew) (Diptera Phoridae) in Italian dairies is reported. Notes on diagnostic features, biology, distribution and economic relevance of the parasitoid are given.